Study of thermocycling effect on the bond strength between an aluminous ceramic and a resin cement Estudo do efeito da ciclagem térmica na resistência da união adesiva entre uma cerâmica aluminizada e um cimento resinoso - Osvaldo Daniel Andreatta Filho; Maria Auxiliadora Junho de Araújo; Marco Antonio Bottino; Renato Sussumu Nishioka; Marcia Maciel Menezes (University of São Paulo, 2005)
This study evaluated the effect of thermocycling on the bond strength between Procera AllCeram (Nobel-Biocare) and a resin cement (Panavia F, Kuraray CO). Nine ceramic blocks with dimensions of 5x6x6mm were conditioned at one face with Rocatec System (Espe). After, they were luted with Panavia F to composite resin blocks (Clearfil AP-X, Kuraray CO). The nine groups formed by ceramic, cement and composite resin were split up obtaining 75 samples with dimensions of 12x1x1mm and adhesive surface presenting 1mm²±0.1mm² of area. The samples were divided into 3 groups (n=25): G1 - 14 days in distilled water at 37ºC; G2 - 6,000 cycles in water (5ºC - 55ºC - 30s); G3 - 12,000 cycles in water (5ºC - 55ºC - 30s). The samples were tested in a universal testing machine (EMIC) at a crosshead speed of 1mm/min. Data were analyzed by ANOVA and Tukey tests. The results indicated that mean values of rupture tension (MPa) of G1 (10.71 ± 3.54) did not differ statistically (p <5%) from G2 (9.01 ± 3.90), however there was statistical difference between G1 and G3 (7.28 ± 3.00). It was concluded that thermocycling significantly reduced the bond strength values when samples were submitted to 12,000 cycles. Este trabalho avaliou o efeito da ciclagem térmica sobre a resistência adesiva entre a cerâmica aluminizada (Procera AllCeram, Nobel-Biocare) e um cimento resinoso (Panavia F, Kuraray CO). Nove blocos de cerâmica, com dimensões de 5x6x6mm, foram condicionados em uma de suas faces com o Sistema Rocatec (ESPE). A seguir foram cimentados a blocos de resina composta (Clearfil AP-X, Kuraray CO). Os conjuntos cerâmica-cimento-resina foram cortados em 75 corpos-de-prova com formato retangular com dimensões de 12x1x1mm e superfície adesiva apresentando 1mm² ± 0,1mm². Os corpos-de-prova foram divididos em três grupos (n=25): G1 - 14 dias em água destilada a 37ºC, G2 - 6000 ciclos em água (5ºC e 55ºC) e G3 - 12000 ciclos em água (5ºC e 55ºC). Os corpos-de-prova foram ensaiados sob velocidade de 1mm/min em máquina de ensaio universal (EMIC). Os dados foram tratados estatisticamente com os testes de Anova e Tukey e indicaram que os valores médios de tensão de rupturas (MPa) de G1 (10,71 ± 3,54) não diferiram estatisticamente (p < 5%) de G2 (9,01 ± 3,90), porém houve diferença significativa entre G1 e G3 (7,28 ± 3,00). Concluiu-se que a ciclagem térmica diminuiu a resistência adesiva significativamente quando os corpos-de-prova foram submetidos a 12000 ciclos.